Legal Protection of Contract Workers in the Work Agreement in Jayagiri Hotel - Feranika Anggasari Jayanti; Johannes Ibrahim Kosasih; I Ketut Widia (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2021)
The development of the tourism industry in Bali causes the high competitiveness of classy hotels such as the Jayagiri Hotel and has an impact on the income aspect of the hotel business, in this case the company's income and leads to legal protection of the rights and obligations given to its workers. This study aims to examine the contractual relationship between contract workers in a work agreement at Jayagiri Hotel and to examine the legal protection can be given for contracts made by the parties and obstacles are experienced by workers in obtaining their rights and obligations. The method used in this study is normative and empirical research method. The results of this study showed that the employment agreement between contract workers and the Hotel has not yet provided a good working relationship so that the application of Law No. 13 of 2003 concerning Employment has not been accommodated. This is due to the entry into force of the standard contract agreement in Jayagiri Hotel which has not provided a balanced position in the same position between workers and employers. Employers as employers always have a higher bargaining position than workers, so the formulation of work agreements in Law No. 13 of 2003 concerning Employment has not been properly accommodated to protect workers' rights and cannot yet prosper workers in accordance with the mandate of the Act.